Game injuries in relation to game schedules in the National Basketball Association - Teramoto, M.; Cross, C. L.; Cushman D. M.; Maak, T. G.; Petron, D. J.; Willick, S. E. (Journal of Science and Medicine in Sport, 2017)
Objectives: Injury management is critical in the National Basketball Association (NBA), as players experience a wide variety of injuries. Recently, it has been suggested that game schedules, such as back-to-back games and four games in five days, increase the risk of injuries in the NBA. The aim of this study was to examine the association between game schedules and player injuries in the NBA. Design: Descriptive epidemiology study. Methods: The present study analyzed game injuries and game schedules in the 2012-13 through 2014-15 regular seasons. Game injuries by game schedules and players` profiles were examined using an exact binomial test, the Fisher`s exact test and the Mann-Whitney-Wilcoxon test. A Poisson regression analysis was performed to predict the number of game injuries sustained by each player from game schedules and injured players` profiles. Results: There were a total of 681 cases of game injuries sustained by 280 different players during the three years (total N = 1443 players). Playing back-to-back games or playing four games in five days alone was not associated with an increased rate of game injuries, whereas a significant positive association was found between game injuries and playing away from home (p < 0.05). Playing back-to-back games and away games were significant predictors of frequent game injuries (p < 0.05). Conclusions: Game schedules could be one factor that impacts the risk of game injuries in the NBA. The findings could be useful for designing optimal game schedules in the NBA as well as helping NBA teams make adjustments to minimize game injuries. AUTORREFERAT